2015
DOI: 10.1038/srep16492
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 mediates TGF-β-dependent crosstalk between hepatic stellate and cancer cells via FAK signaling

Abstract: Transforming growth factor-β (TGF-β) signaling plays a key role in progression and metastasis of HCC. This study was undertaken to gain the proof of concept of a small-molecule inhibitor of TGF-β type I receptor kinase, EW-7197 as a potent anti-cancer therapy for HCC. We identified tissue inhibitors of metalloproteinases-1 (TIMP-1) as one of the secreted proteins of hepatic stellate cells (HSCs) and a key mediator of TGF-β-mediated crosstalk between HSCs and HCC cells. TGF-β signaling led to increased expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
(56 reference statements)
1
45
0
Order By: Relevance
“…Previous research asserted that hepatocytes were activated at 2 h of LR after PH, and their transition from G0 phase to cell cycle occurred at 2–6 h [ 43 ] ILK pathway could activate the nuclear translocation of β-catenin and enhanced the transcription of LEF-1 through integrin-linked kinase pathway, and then increase the activity of Ap-1 which could promote cell proliferation [ 44 , 45 ], and the expression of critical cytokine IL-6 [ 46 , 47 ] which could affect cell proliferation via Stat3 signal pathway. It has demonstrated that transforming growth factor-β (TGF-β) signaling plays a key role in progression and metastasis of HCC [ 48 , 49 ], and it influences the expression of smad4, smad2/3, and β-catenin proteins and regulates cell activities [ 49 ], which indicates that it is important in liver cells. McCubrey et al pointed out that ERK / MAPK pathway, as the most classic pathway in mitogen-activated protein kinases (MAPKs) pathways [ 50 ], had significant function in cells [ 51 ], and played a key function in tumor cell proliferation, differentiation, survival, migration, and angiogenesis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research asserted that hepatocytes were activated at 2 h of LR after PH, and their transition from G0 phase to cell cycle occurred at 2–6 h [ 43 ] ILK pathway could activate the nuclear translocation of β-catenin and enhanced the transcription of LEF-1 through integrin-linked kinase pathway, and then increase the activity of Ap-1 which could promote cell proliferation [ 44 , 45 ], and the expression of critical cytokine IL-6 [ 46 , 47 ] which could affect cell proliferation via Stat3 signal pathway. It has demonstrated that transforming growth factor-β (TGF-β) signaling plays a key role in progression and metastasis of HCC [ 48 , 49 ], and it influences the expression of smad4, smad2/3, and β-catenin proteins and regulates cell activities [ 49 ], which indicates that it is important in liver cells. McCubrey et al pointed out that ERK / MAPK pathway, as the most classic pathway in mitogen-activated protein kinases (MAPKs) pathways [ 50 ], had significant function in cells [ 51 ], and played a key function in tumor cell proliferation, differentiation, survival, migration, and angiogenesis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…With positive feed-back loop, the activated HSCs, but also Kupffer cells, macrophages and platelets are responsible for the secretion of TGF-β that in turn activates more HSCs. As a result, the production and the release of ECM molecules, tissue MMPs, such as MMP2, 9, and 13, and MMPs inhibitors, such as TIMP1, are increased [67][68][69]. Tumor cells can induce remodeling by stromal cells through altered signaling pathways.…”
Section: Inflammation and Tissue Remodelingmentioning
confidence: 99%
“…TIMP1 is also involved in the cell proliferation, antiapoptotic function, angiogenesis, and oncogenesis (Ries, 2014). Moreover, TIMP1 has been shown to be overexpressed in multiple cancer types and acts as a therapeutic target for GC and other cancers (Omar et al, 2018;Park et al, 2015;Toricelli et al, 2017). The SPARC gene encodes a cysteine-rich acidic matrix-associated protein, which is required for the collagen and is also involved in extracellular matrix synthesis and promotion of changes to cell shape (Morrissey et al, 2016).…”
Section: Survival Analysis Of Nine Hub Genesmentioning
confidence: 99%